REVEAL THE SYNERGY OF INTERNAL AUDIT AND WHISTLEBLOWING SYSTEM IN FRAUD PREVENTION - Frida Aini Nastiti; Zakhir Wikan Anadiya (RADJA PUBLIKA, 2025)
As fraud becomes increasingly intricate, organizations must devise robust prevention strategies. By establishing effective measures against fraud, organizations can safeguard themselves from fraudulent activities and enhance their credibility and reputation. This research seeks to uncover the collaborative effect of internal audits and whistleblowing systems in curbing fraud within organizational settings. The study employs a literature review with a descriptive qualitative approach, analysing various research on the roles of internal audits and whistleblowing in identifying and preventing fraud. The analysis included ten pertinent articles from 2019 to 2024, concentrating on the efficacy of these oversight mechanisms. Findings indicate that internal audits are crucial for internal control and risk assessment, while whistleblowing systems offer a channel for reporting misconduct that formal systems might overlook. By combining these two elements, a complementary approach is created that can enhance the efficiency of fraud prevention. This research suggests bolstering the internal audit function and establishing reliable whistleblowing systems as essential strategies for upholding organizational integrity and transparency. Future research needs to be strengthened by combining external audits of the whistleblowing system in fraud prevention to obtain more in-depth results.